A resolução de problemas como metodologia de ensino para os professores de matemática da cidade de Itabaiana-PB. - Souza, Michely Nascimento de. (2013)
The objective of this study was to identify the knowledge that the mathematics teachers of Basic Education of the City of Itabaiana-PB has with respect to the methodology of troubleshooting. According to Van de Walle (2009) through this teaching methodology should be the focus of the mathematics curriculum, being seen as the main teaching strategy, since it must begin where the students are always taking into account the expertise they bring to the classroom in order to make this practice an effective method of teaching and learning. A questionnaire was applied in order to identify how the teacher works with the resolution of problems as well as raising the difficulties encountered by faculty with this methodology when applied in the classroom. The results obtained in the questionnaire revealed that most teachers recognize the importance of this method for teaching and learning of mathematicsand use it positively, although finding it difficult by students, such as reading and interpretinghe description of the problem, what causes failure according to the teachers in implementing he methodology in the classroom.